2021
DOI: 10.3390/biom11121754
|View full text |Cite
|
Sign up to set email alerts
|

Are Uropathogenic Bacteria Living in Multispecies Biofilm Susceptible to Active Plant Ingredient—Asiatic Acid?

Abstract: Urinary tract infections (UTIs) are a serious health problem in the human population due to their chronic and recurrent nature. Bacteria causing UTIs form multispecies biofilms being resistant to the activity of the conventionally used antibiotics. Therefore, compounds of plant origin are currently being searched for, which could constitute an alternative strategy to antibiotic therapy. Our study aimed to determine the activity of asiatic acid (AA) against biofilms formed by uropathogenic Escherichia coli, Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Asiatic acid showed in vitro anti-mycobacterial activity against Mycobacterium tuberculosis H37Ra, Mycobacterium bovis BCG and Mycobacterium smegmatis [ 105 ]. Bacteria causing urinary tract infections such as Escherichia coli , Enterobacter cloacae and Pseudomonas aeruginosa showed a decrease in survival and a weakened ability to create biofilms demonstrating significant effects of asiatic acid on bacterial cell survival [ 106 ]. Previously, this compound also increased the susceptibility of Pseudomonas aeruginosa biofilms to tobramycin [ 107 ].…”
Section: Antimicrobial Activity Of Asiatic Acidmentioning
confidence: 99%
“…Asiatic acid showed in vitro anti-mycobacterial activity against Mycobacterium tuberculosis H37Ra, Mycobacterium bovis BCG and Mycobacterium smegmatis [ 105 ]. Bacteria causing urinary tract infections such as Escherichia coli , Enterobacter cloacae and Pseudomonas aeruginosa showed a decrease in survival and a weakened ability to create biofilms demonstrating significant effects of asiatic acid on bacterial cell survival [ 106 ]. Previously, this compound also increased the susceptibility of Pseudomonas aeruginosa biofilms to tobramycin [ 107 ].…”
Section: Antimicrobial Activity Of Asiatic Acidmentioning
confidence: 99%
“…Weak AA activity has been described for Gram-positive strains of E. faecalis [ 46 , 63 ] and S. aureus [ 63 ]. Gram-negative strains of E. coli , P. aeruginosa , and E. cloacae as well as Gram-positive S. aureus showed the lowest sensitivity to AA (MIC >128 mg/L) [ 9 , 63 , 64 ]. Among these strains were uropathogenic E. coli , for which the AA MIC ranged from 512 mg/L to >1024 mg/L [ 9 , 10 , 47 ].…”
Section: Antibacterial Properties Of Pentacyclic Triterpenesmentioning
confidence: 99%
“…The recent study of Sycz et al [ 9 ] revealed that AA decreased the survival and the ability to create single- and multi-species biofilms by uropathogenic E. coli CFT073, E. cloacae ATCC-BAA 2468, P. aeruginosa ATCC 25000 strains. AA also changed the morphology of these bacteria.…”
Section: Anti-biofilm Properties Of Pentacyclic Triterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most active constituents in Centella asiatica (L.) Urb, asiatic acid can show significant broad-spectrum antibacterial activity on Escherichia coli , Salmonella typhimurium , Pseudomonas aeruginosa , Enterococcus faecalis , S. aureus , etc. [ 13 , 14 , 15 , 16 ]. However, our research confirmed that another main compound in Centella asiatica (L.) Urb, MA, also showed significant antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%